The need and importance of inter-faith dialogue in the light of Sira-e-Taiba - Dr.Shakir Hussain Khan, (BNBWU Journal of Multidisciplinary Research, 2025)
Interfaith dialogue has become the need of the hour. Dialogue is the only means through which we can convey the call of our religion to others. Dialogue is the only means by which we can learn about the beliefs of others. Dialogue is a style of preaching through which the preacher can compel an audience to contemplate seriously. Dialogue is a method of communication in which there is direct communication between the speaker and the listener. Through dialogue, the real facts come out. Relationships can be developed through dialogue with those belonging to different religions of the world. From the Qur'anic teachings and the biography of Rasulullah (S.A.W.W) , we get an explanation of the need and importance of dialogue.By following which we can make the world a cradle of peace. I have highlighted the need and importance of interfaith dialogue in the light of Sira e Tayyaba in my paper.